Anthropogenic implications for land cover changes and vegetation structure in coastal protected forest - SYAIFUL EDDY; INKA DAHLIANAH; CONNY MASHITO; MAHARANI OKTAVIA; BUDI UTOMO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Eddy S, Dahlianah I, Mashito C, Oktavia M, Utomo B. 2022. Anthropogenic implications for land cover changes and vegetation structure in coastal protected forest. Biodiversitas 23: 4473-4481. Anthropogenic activities in coastal areas have largely eliminated mangrove forest cover, including the Air Telang Protected Forest (ATPF). This study aims to analyze land cover changes in 2021 and the vegetation structure in ATPF which covers an area of ??approximately 12,660.87 ha. The method used in this study is a survey method with two stages of data collection, namely the collection of image data and vegetation data. Image data for 2021 was obtained from Landsat 8 Oli, while vegetation data were collected through the identification of plant species and quantitative analysis through the calculation of the Important Value Index (IVI) and the Shannon Diversity Index (H?). The results of this study show that there has been deforestation in ATPF by 66.4% until 2021 due to land conversion into coconut plantations, oil palm plantations and open areas. The number of plant species obtained was 20 species consisting of seven true mangrove species and 13 associated mangrove species. The diversity index ranges from 0.00 to 0.62 which is included in the low category.